DNA barcoding the ichthyofauna of the Yangtze River: Insights from the molecular inventory of a mega‐diverse temperate fauna. (12th June 2019) - Shen, Yanjun; Hubert, Nicolas; Huang, Yan; Wang, Xuzheng; Gan, Xiaoni; Peng, Zuogang; He, Shunping
Abstract: Intensification of inland fisheries and aquatic landscape conversion led to a drastic decline of fish populations in the Yangtze River (YR) during the last decades. This situation urges for the development of a large‐scale molecular assessment of YR ichthyofauna to further develop standardized methods of molecular identification for conservation and fisheries management purposes. We present here the results of a large‐scale campaign to DNA barcode YR freshwater fishes that succeeded in producing 1, 424 new DNA barcodes for 123 species. Together with 1, 406 sequences mined from BOLD and GenBank, a reference library including 2, 830 DNA barcodes for 238 species was compiled. By using four DNA‐based species delimitation methods, RESL, ABGD, mPTP and mGMYC, 230 operational taxonomic units (OTUs) were identified and 195 species displayed OTUs that tightly match species boundaries. No barcoding gap was observed; however, and conflicting cases of species and OTU delimitation were identified. A total of 23 species with maximum intraspecific distances above 2% were detected and null genetic distances to the nearest phylogenetic relatives were detected in 11 species. Among those 23 species, 16 were represented by multiple OTUs amounting to 40 OTUs delineated. Several cases of multiple OTUs confined to species boundaries were detected suggesting the presence of overlooked species. A total of 18 OTUs, however, were shared by several species and particularly so for the Qinghai‐Tibet plateau endemic species. These results are discussed with reference to previous large‐scale DNA barcoding campaign and compared to previous phylogeographic studies in the YR.